2023
DOI: 10.1002/smll.202301267
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Etching‐Doping Route to Fe/Mo Co‐Doped Ni Oxyhydroxide Catalyst for Enhanced Oxygen Evolution Reaction

Abstract: Fe‐doped Ni (oxy)hydroxide shows intriguing activity toward oxygen evolution reaction (OER) in alkaline solution, yet it remains challenging to further boost its performance. In this work, a ferric/molybdate (Fe3+/MoO42−) co‐doping strategy is reported to promote the OER activity of Ni oxyhydroxide. The reinforced Fe/Mo‐doped Ni oxyhydroxide catalyst supported by nickel foam (p‐NiFeMo/NF) is synthesized via a unique oxygen plasma etching‐electrochemical doping route, in which precursor Ni(OH)2 nanosheets are f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…89 Moreover, Ir/Fe co-doping can reduce the OER energy barrier over Co(OH) 2 by promoting the formation of the *O intermediate. 68 Similar results that emphasize the role of dual cation dopants in regulating active sites' electronic environments and optimizing the adsorption strength of reaction intermediates have been evidenced by Li et al 90 and Wei et al 91 Of note, the cation dopants can also work as highly active sites toward OER. For instance, the V site in V/Fe co-doped NiOOH has near-optimal binding energies toward intermediates and shows a lower energy barrier than Ni or Fe sites.…”
Section: Cation-cation Dual-doped Metal (Hydr)oxidessupporting
confidence: 64%
“…89 Moreover, Ir/Fe co-doping can reduce the OER energy barrier over Co(OH) 2 by promoting the formation of the *O intermediate. 68 Similar results that emphasize the role of dual cation dopants in regulating active sites' electronic environments and optimizing the adsorption strength of reaction intermediates have been evidenced by Li et al 90 and Wei et al 91 Of note, the cation dopants can also work as highly active sites toward OER. For instance, the V site in V/Fe co-doped NiOOH has near-optimal binding energies toward intermediates and shows a lower energy barrier than Ni or Fe sites.…”
Section: Cation-cation Dual-doped Metal (Hydr)oxidessupporting
confidence: 64%
“…1i and S10, ESI,† I 481 / I 563 of Ni(OH) 2 @NF-0.9 and Ni(OH) 2 @NF-1.0 were practically equivalent under 1.38 V RHE , 1.40 V RHE , 1.42 V RHE and 1.44 V RHE , while being significantly larger than that of Ni(OH) 2 @NF-1.2. It has been reported that the larger I 481 / I 563 should be associated with the higher proportion of γ-NiOOH generated from the anodic oxidation process, 58–63 which confirms the greater ratio of α-Ni(OH) 2 within Ni(OH) 2 @NF-0.9 and Ni(OH) 2 @NF-1.0 than that of Ni(OH) 2 @NF-1.2. This phenomenon possibly originated from the higher local pH for Ni(OH) 2 @NF-1.2 during the HER-derived synthetic process under a more negative cathodic potential of −1.2 V Ag/AgCl , which induces the aging process of α-Ni(OH) 2 to produce β-Ni(OH) 2 .…”
Section: Resultsmentioning
confidence: 58%
“…A detailed comparison of the intensity ratio of two Ni III –O bands centered at 481 and 563 cm −1 ( I 481 / I 563 ) reveals the difference in Ni(OH) 2 phase composition for the three materials. 58–63 As is illustrated in Fig. 1i and S10, ESI,† I 481 / I 563 of Ni(OH) 2 @NF-0.9 and Ni(OH) 2 @NF-1.0 were practically equivalent under 1.38 V RHE , 1.40 V RHE , 1.42 V RHE and 1.44 V RHE , while being significantly larger than that of Ni(OH) 2 @NF-1.2.…”
Section: Resultsmentioning
confidence: 84%
“…In contrast, the Raman peaks at ∼454 cm −1 and 525 cm −1 of the NiFeMo-LDH catalyst were attributed to Ni II –O vibrations at OCP. 21,73 A slightly weak peak signal at 910 cm −1 corresponds to the vibration of Mo–O bonds, and the intensity of the peak decreases slightly with the increase of the potential and seemingly disappears in the Raman diagram at 1.60 V. 74,75 As the potential increases, a notable change in the Raman peaks occurs at 1.30 V, with the emergence of characteristic Ni III –O peaks at 480 cm −1 and 560 cm −1 , gradually becoming dominant at higher potentials. This indicates the initiation of NiOOH phase formation under the influence of a high applied potential.…”
Section: Resultsmentioning
confidence: 99%